Poultry Value Chain in Two Medium-Sized Cities in Kenya; Insights From Cluster Theory - Omondi, Samuel Onyango (Frontiers in Veterinary Science, 2022)
Poultry is an attractive enterprise among urban smallholder farming households and is the most common livestock reared for home consumption and sale. By combining cluster and value chain approaches, the study analyses the operation of poultry value chain in medium-sized cities of Thika and Kisumu, Kenya. The study draws on a survey of 312 urban poultry producing households as well as qualitative interviews with key stakeholders in the urban poultry value chain. Spot market is the predominant governance structure in the poultry value chain in Thika and Kisumu. Farmers and traders employ various upgrading mechanisms to maintain their competitiveness. However, some producers and traders engage in illegal activities such as theft of poultry, illegal slaughtering and sale of adulterated low-quality poultry feed. Results also show that poultry producers in Thika enjoy the benefits of being located in a cluster of feed millers and close proximity to output market.